2016
DOI: 10.1016/j.foodpol.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Universal food security program and nutritional intake: Evidence from the hunger prone KBK districts in Odisha

Abstract: HighlightsThis paper provides evidence on the link between consumer subsidy and nutrient intake.We compare districts with a targeted versus universal subsidy entitlements.Universalization of PDS in some of the poorest districts led to greater nutrient intake and diet quality.These results have important implications for the National Food Security Act in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 21 publications
1
32
1
Order By: Relevance
“…Tackling food insecurity is the first step towards improving diets and, in this regard, it is heartening that India's National Food Security Act (NFSA) 2013 seeks to cover up to 75 per cent of rural and 50 per cent of the rural and urban population respectively under the PDS. In a recent contribution, Rahman () establishes a robust link between consumption of subsidized food grains from PDS and nutrient intake. He argues that that the savings resulting from purchases at PDS shops where prices are lower as compared to open market prices could be spent by households on nutritious foods.…”
Section: Discussionmentioning
confidence: 99%
“…Tackling food insecurity is the first step towards improving diets and, in this regard, it is heartening that India's National Food Security Act (NFSA) 2013 seeks to cover up to 75 per cent of rural and 50 per cent of the rural and urban population respectively under the PDS. In a recent contribution, Rahman () establishes a robust link between consumption of subsidized food grains from PDS and nutrient intake. He argues that that the savings resulting from purchases at PDS shops where prices are lower as compared to open market prices could be spent by households on nutritious foods.…”
Section: Discussionmentioning
confidence: 99%
“…the districts of Angul, Bargarh, Balesore, Cuttack, Deogarh, Bhadrak, Jajpur, Ganjam, Khordha, Dhenkanal, Jharsuguda, Puri, Sambalpur, Jagatsingpur, Keonjhar, Sundergarh, Kendrapara, Mayurbhanj and Nayagarh). The 11 KBK + south districts are largely populous with indigenous communities (namely 'adivasis' and/ or tribal), interior of the district is mountainous, have historically deprived economy and poor health indicators, poor access to transport facilities that hinders health care delivery and extremely food insecure than non KBK + districts 19 . The availability of nurses in the state is also very low.…”
Section: Context Of India With Specific Emphasis To Odisha Statementioning
confidence: 99%
“…Evaluations of the MDMS has shown its effectiveness in reducing undernutrition of school-aged children, especially from families who suffered from shocks such as droughts (Singh, Park, & Dercon, 2013). Rahman (2016) and Kishore and Chakrabarti (2015) have linked universal access to the PDS with greater household diet diversity. However, in a study by Kaushal and Muchomba (2015), the author found that PDS access may not have a clear impact on nutrition outcomes.…”
Section: Improving Access To Food Diversitymentioning
confidence: 99%